Особенности решения задачи маршрутизации с учетом технологии traffic engineering для сетей, представленных соединенным графом - Вавенко, Т. В. (ХНУРЭ, 2011)
This work is devoted to the problem of routing taking into account the load balancing for networks, which are presented as connecting graph. This paper contains a mathematical formulation of flow model of multipath routing with load balancing of technology Traffic Engineering. We study the telecommunication network which consists of several subnetworks, which are connecting to each other. We identified problems that occur when solving the problem of routing for such networks, identified the causes of it and propose solutions.
Keywords: объем информационного трафика; мультисервисное обслуживание трафика